Hydrothermal Synthesis of ZSM⁃5 Induced by Corresponding Alkaline Hydrolysis Products - Wenqi XU; Yifan LIU; Jiaxin MA; Rui WANG; Heng JIANG; Changzi JIN (Liaoning Shiyou Huagong Daxue xuebao)
ZSM⁃5 has been widely used in the field of petrochemical industry. The extensive use of organic templates in its conventional synthesis process has caused serious problems on environmental and cost. In this paper, the hydrothermal synthesis of ZSM⁃5 with tetraethyl orthosilicate, aluminum sulfate octadecahydrate and alkaline hydrolysis product of HZSM⁃5 as silica source, alumina source and structural directing agent, respectively, has been investigated, which aims at developing of new process for green synthesis of zeolites. The synthesized samples were characterized by a series of techniques, such as XRD, TEM, SEM, N2 physical adsorption and TG analysis. It has been shown that successful synthesis of ZSM⁃5 can be achieved by induction of alkaline hydrolysis product of HZSM⁃5 in organic template⁃free system. The prepared sample possesses a relative low crystallinity and specific surface area than ones from conventional process. The study in this paper has provided the chance for combination of green synthesis of zeolites and post⁃treatment route for synthesis of hierarchical zeolites.